Media construction of Russia's international relations: specifics of representations. Issue 1 (1st January 2017) - Dubrovskaya, Tatiana; Kozhemyakin, Evgeniy
ABSTRACT: This paper discusses the mechanisms of discursive construction of Russia's international relations and intends to identify such mechanisms in the media. Using the framework that is informed by social constructionism and Critical Discourse Analysis, the authors view international relations as a discursive phenomenon, which is constructed through a specific repertoire of pragmalinguistic means. Drawing on the Russian foreign minister's speech and its representations in Russian newspapers, the authors conduct a case study analysis and reveal that the representations of international relations undergo recontextualisation in the media as compared to the representations in proper diplomatic discourse. The newspapers offer avenues for ideologically charged interpretations through chronotope representations and the strategy of emotionalisation. The media also widen the discursive context of international relations by way of the inclusion of heterogeneous social actors, which are grouped in a way that discloses a conflict potential in their relations.